The association between weight-adjusted-waist index and increased urinary albumin excretion in adults: A population-based study - Qin, Zheng; Chang, Kaixi; Yang, Qinbo; Yu, Qiao; Liao, Ruoxi; Su, Baihai (Frontiers in Nutrition, 2022)
Aims: The negative effect of obesity on kidney health has been reported. The association between weight-adjusted-waist index (WWI, a newly developed adiposity index) with albuminuria has not been reported before. Methods: The present cross-sectional study was conducted among adults with complete data about WWI and urinary albumin-to-creatinine ratio (ACR) in 2005-2018 National Health and Nutrition Examination Survey (NHANES). WWI was calculated as waist circumference (WC) divided by the square root of weight. Weighted multivariable logistic regression and generalized additive model were employed to explore the independent relationship between WWI with albuminuria and its non-linearity. A two-piecewise linear regression model was used to calculate the threshold effect. Subgroup analysis and interaction tests were also performed. Results: A total of 36921 participants were enrolled with a prevalence of albuminuria of 9.32%. The prevalence of albuminuria increased with the higher WWI tertiles (Tertile 1: 5.31%, Tertile 2: 8.23%, Tertile 3: 15.65%). WWI was positively associated with a higher likelihood of albuminuria (OR = 1.28, 95% CI: 1.15-1.43) and this relationship reminds stable in subgroups (all P for trend >0.05). Nonlinear positive relationships were detected in females with a breakpoint of 10.93. A positive association between WWI with albuminuria (OR=1.39, 95% CI: 1.20-1.61) was observed on the right of breakpoint, while the association on the left was of no statistical significance. WWI showed a stronger correlation with albuminuria (OR = 1.28) than other markers of obesity including body mass index (BMI, OR=1.02) and WC (OR=1.01). Conclusion: WWI levels positively related with increased likelihood of albuminuria in US adults and showed a stronger relationship than BMI and WC. Our findings indicated that WWI may serve as a simple anthropometric index to predict albuminuria.